On the Contribution of Developed Capitalist Countries to International Economic Security in the Era of Civilizational Confrontation - A. A. Kovalev (Управленческое консультирование)
The purpose of the study — the study and systematization of the main approaches to the problem of economic security on the example of the leading countries of the world economy — causes the following tasks: 1) identify and assess the forms and means by which developed capitalist countries solve the most important issues of their own economic security; 2) identify the contribution of these countries to the creation of an integrated system of international economic security. Research methods include methods of political, sociological and cultural analysis, as well as a comparative approach. Results. The article deals with the peculiarities of the practical implementation of the state of economic security in the developed countries of Western civilization (USA, Canada, Germany, France, great Britain, Spain, Italy, Japan), the main strategic goal of which in the field of protection of national economic interests is to ensure sustainable economic growth and economic reform in accordance with the conditions of competition in the world market. The main attention of the European Union countries is paid to ensuring national security through a holistic process of achieving European security, but the leadership of the European Union is not always able to ensure the integral security of its member States due to both internal contradictions and emerging problems with the United States, which subordinate the economic interests of European States to the satisfaction of their own political ambitions. Findings. In the countries of Western civilization, after the integration processes of the last three decades, the economic security of a developed capitalist country is not seen as a state of complete independence from the rest of the world, but as a state of stable and sustainable socio-economic development, which can be achieved through close political and economic cooperation. But the desire for the fullest possible independence from the United States of America — both national economies and their own domestic and foreign policies — in the developed countries of Europe is intensifying in times of crisis. The global economic crisis that broke out in 2008 also led to systemic and structural problems in the developed countries of Western civilization, which today are not possible to solve. The oldest European democracies are built into the world security system as the basic elements of the American geopolitical strategy. To date, there is no integral system of international economic security that would take into account the interests of at least developed countries of Western civilization.